Wyznaczniki kształtujące sytuację ucznia z niepełnosprawnością w klasie ogólnodostępnej i integracyjnej – analiza dostępnych badań - Bartnikowska, Urszula; Ćwirynkało, Katarzyna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Integrative/inclusive education has become a reality, but its effects on students with disabilities are not always obvious. The paper, which is based on the analysis of available research, shows multidimensional determinants of the success of school integration/inclusion of students with disabilities. The authors focused on the main aspects: school achievement and peer relationships which shape the situation of these students.